Vertical transmission of Toxoplasma gondii in Australian marsupials - Parameswaran, N. (2009)
To date, little is known about the dynamics of vertical transmission of Toxoplasma gondii in Australian marsupials. Studies in mice demonstrate that vertical transmission of T. gondii is common and that chronically infected mice can transmit T. gondii to successive generations. In this study, PCR and immunohistochemistry were used to detect T. gondii in chronically infected marsupial dams and their offspring. T. gondii was detected in the unfurred pouch young of 2 out of 10 chronically infected western grey kangaroos (Macropus fuliginosus) and in the unfurred pouch young of a brush-tailed bettong (Bettongia penicillata). Results of the study suggest vertical transmission of T. gondii can occur in chronically infected Australian marsupials.